Implementation of Matang Teupah Village Regulation No. 12 of 2010 Concerning Chicken Farming Business Permit According to Fiqh Siyasah - T. Wildan (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2022)
This research will answer, how is the implementation of the Matang Teupah Village Regulation No. 12 of 2010 concerning the business license for chicken farming, how is the environment for the poultry farm business in Matang Teupah Village according to Fiqh Siyasah. This research is field research and manuscript analysis and this type of research uses descriptive qualitative methods. The results of the study are: the efforts of the Matang Teupah Village Government and the Aceh Tamiang District Government in controlling environmental pollution caused by the community who have a broiler business have been going quite well because the Village Government has made several efforts in accordance with government regulations in controlling the waste pollution. and set forth in Village Regulations so as to be able to maintain the surrounding environment free from waste pollution. In view of fiqh siyasah environmental pollution carried out by the community in Matang Teupah Village, in not accordance with Islamic law, because humans as caliphs on earth are to be able to prosper the earth in accordance with Islamic law and preserve it. In the view of Islam, the caliph is responsible for himself, he must also bear the responsibility of his fellow living creatures and the whole of nature, including in maintaining the sustainability of the existing environment.